EDUKASI LITERASI KEUANGAN DI KOMUNITAS TDA PEREMPUAN (TANGAN DI ATAS) KOTA MALANG - Ermayda, Ria Zulkha; Trisnawati, Novi; Fatmasari, Devi Sinta; Mulyadi, Dhiki (Universitas Mataram, 2024)
Financial literacy plays an important role in decision-making and financial management, both individually and in groups. The TDA (Tangan Di Atas) Malang community plays a role in national economic growth efforts which is the same as financial literacy, namely contributing to economic growth and state development through improving service quality. Good financial literacy in entrepreneurs will make the business more focused and clear to achieve wealth. This activity aims to support economic growth through financial literacy education so that TDAP Malang members can improve their understanding and have the knowledge and skills of good financial management. The methods used in overcoming financial literacy problems are the lecture method and the demonstration/simulation method. The lecture method is in the form of delivering theories and concepts about current financial management. While the demonstration/simulation method shows how to manage finances in the form of applying Ms Excel software. It is known that the distribution of the latest education level of the participants at the S1 (undergraduate) education level is 85%. At the high school / vocational high school education level by 11% and the smallest presentation at the Diploma education level (D1 / D2 / D3) by 4%. Some types of businesses run are mostly engaged in food and beverage with a percentage of 63% and services / trade at 37%. The implementation team also identified the age/length of the business that had been established. Divided into 3 parts, namely businesses that run less than 1 year (< 1 year), 1-5 years, and more than 5 years (> 5 years). It was found that 52% of businesses established were more than 5 years old, 44% had been established between 1-5 years, and 4% were less than 1 year old. This service activity provides an understanding and implementation of financial management to TDAP Malang to support economic growth and support the sustainability of MSMEs.